COMPLIANCE ON EVENTS SUBSEQUENT TO THE FINANCIAL STATEMENTS - Vílchez Olivares, Percy Antonio (2016)
According to accounting regulations issued in our country, companies listed on the Lima Stock Exchange began a process of adopting the International Financial Reporting Standards (IFRS for its acronym in English) from the year 2011, these rules are issued by the Financial Accounting Standards Board (IASB for its acronym in English), with the exception of banking enterprises, financial and insurance companies and others regulated by the Superintendence of Banking and Insurance. This research aims to analyze the industrial companies’ degree of compliance and utilities listed on the Lima Stock Exchange in adoption of the IFRS regarding the accounting disclosures required by the IASB 10, Events occurred after the 2015 reported period. The results show that there is a partial information deficiency and provide significant evidence of relevant normative categories over financial events occurred after the reported period that are affected in compliance of the IFRS.